Nanoemulgel Formulation of Eleutherine palmifolia Onion Bulb Extract and Its Effectiveness in Wound Healing - Muhammad Faisal; Lutfi Chabib; Melynia Sintha Dewi; Michael Raharja Gani; Rini Dwiastuti (Sanata Dharma University, 2024)
Eleutherine palmifolia onion, an indigenous medicinal plant from Borneo, is empirically applied to treat wound healing. The objective of this study is to formulate its extract and assess its in vivo wound healing activity. Eleutherine palmifolia onion was extracted with a 96% ethanol solvent. The extract of the Dayak onion bulb was then formulated into a nanoemulsion by applying the DOE method of 2-level factorial design. Four nanoemulsion formulations were further analyzed to obtain the optimal formulation. The particle size analysis and % transmittance was performed using a particle size analyzer and an ultraviolet-visible spectrophotometer. Furthermore, the data were analyzed using the Minitab 19 application with the DOE factorial design method. The three nanoemulgel formulations containing 2.5, 5.0, and 7.5% extract were further investigated for wound healing efficacy in rats. The duration of wound closure was analyzed using paired t-tests. The best nanoemulsion formulation was made with 22.5 mL of Tween 80 and 2 mL of isopropyl myristate oil. This produced particles that were 12.13 nm in size and a 99.12% transmittance rate. Wound length measurements were taken daily for 15 days. The statistical test results of p0.05 indicate that the nanoemulgel of the extract has significant activity in wound healing. The optimal nanoemulsion formula is formula A, and the effective dose of Dayak onion extract nanoemulgel is 5% and 7.5% concentrations, with a wound healing time of 13 days.